ETNOMATEMATIKA: EKSPLORASI MOTIF BEKA BULUH DAN UIS NIPES RAGI BARAT SUKU BATAK KARO TERHADAP KONSEP BANGUN DATAR - Sembiring, Thresia Yohana; Tambunan, Hardi; Simanujuntak, Ruth M (Universitas Quality, 2024)
Mathematical concepts that can be used to explore mathematics in culture. The term used to associate mathematics and culture is ethnomathematics. Cultural elements such as regional dances, regional songs, customs, regional languages, traditional games, traditional food and regional clothing need to be preserved because they can be integrated into the learning process. One of them is the culture found in the Batak tribe, especially the Batak Karo. The richness of the Batak Karo tribe in terms of traditional clothing motifs, namely the beka reed and uis nipes yeast western. The aim of this research is to explore the concept of flat shapes in the beka buluh and uis nipes ragi barat motifs of the Batak Karo tribe. The research was carried out in Tiga Binanga, Karo Regency, North Sumatra Province in December 2023 with sources from the traditional Batak Karo tribe. The data analysis used is observation and interviews. This research is qualitative research with an ethnographic approach. The results of this research found the mathematical concept of flat shapes in the motifs of beka buluh and uis nipes Ragi Barat Batak Karo tribe.